Micromorphological characteristics (anatomical structure of leaves and stems, ultrastructure of fruits, pollen grains ultrasculpture) of Sonchus oleraceus L. (Asteraceae). (CHORNOMORSKI BOTANICAL JOURNAL, 2016)
This article provides detailed study of micromorphological structure of leaves and stems, ultrastructure of fruits, pollen grains ultrasculpture of Sonchus oleraceus using light and scanning electron microscopy. On the one hand, it is revealed the existence of different methods of structural adaptation of plants to grow in mesophytic conditions, and on the other it showed that the investigated species has some features in the structure that can be used by taxonomists. Thus, our study showed that mezomorphic features apparent in the structure of almost all basic tissue complexes of leaf and stem, particularly the coating (large cells of tissues, thin cell walls of almost straight shape, presence of essential oil glands and essential oils in the cells, no pubescence, etc.), a conducting (midrib has several vascular bundles, distinct bearing facing vascular bundles, large cells of tissues of xylem, et al.) and mesophillous (a small number of layers mesophill, large cells of tissues, plenty of intercellular spaces). Palynomorphological study showed that pollen grains trycolporate, medium in size, echinolophate with small spines and fenestrate or perforated ultrasculpture between pore lacunes and on lophate sides. We think that quantitative features (size of pollen grains, spines, pore diameter) may be diagnostic at the species level.
Keywords: Sonchus, Asteraceae.